Persepsi Pengguna Laporan Keuangan terhadap Peran Laporan Audit Kas dan Setara Kas dalam Meningkatkan Kualitas Perusahaan - Abdullah Ariq Akbar; Fajar Yudha Septianto; Muhammad Andra Priatama A.; Ridwan Zulfi Agha (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study focuses on the role of auditing in improving the credibility and reliability of financial statements, particularly through the examination of cash and cash equivalents, which are the most liquid assets and also the most vulnerable to errors and fraud. The purpose of this study is to improve the understanding of financial statement users, including investors, financial analysts, consultants, academics and accounting practitioners, as well as accounting students, about the function of cash and cash equivalents audit reports in improving business quality. This study found that comprehensive and independent cash and cash equivalent audits can increase user confidence in the transparency, accountability, and reputation of companies. This study conducted semi-structured interviews with eight informants in Jakarta, Bogor, and Depok. The results show that three main factors influence financial statement users' perceptions of audit quality: auditor credibility, audit process independence, and the audit's ability to demonstrate good corporate governance. According to the results of this study, cash audits are very important as a measure of management integrity and a tool for assessing company quality. The study is also expected to help auditors and management improve audit practices that are clearer, more independent, and focused on the needs of financial statement users.